Comparison of methods of heating a rotary-film apparatus for the production of vegetable concentrates - Zagorulko, Aleksey; Zahorulko, Andreii; Liashenko, Bogdan; Gordienko, Iryna (Technology audit and production reserves, 2019)
The object of research is the temperature field of the working surface of the rotor-film apparatus (RFA) when heated by a nichrome spiral with a different coolant layer or using a flexible film resistive radiating type electric heater (FFREHRT). Since the concentration of vegetable purees using RFA is a promising solution, due to a significant reduction in processing time and high quality of the resulting products. Today, most RFAs use electric heating of nichromes with spirals with intermediate coolants, to process a uniform heat flow, which is determined empirically for the thickness of the coolant layer depending on the flow of raw materials, it is processed. Such methods make it possible to obtain qualitative indicators of the uniformity of the temperature field, but the problem is an increase in the metal consumption of the apparatus due to the presence of pumps for the movement of coolants, which generally complicates the operating conditions. Therefore, it is important to improve the RFA heating system using FFREHRT, which is also a thermally insulated surface with a uniform distribution of the temperature field over the entire radiation plane. In the course of the study, the uniformity of the temperature distribution in the RFA model sample is determined for various heating methods (nichrome wire with an intermediate coolant, PFMS-4 organosilicon liquid or FFREHRT). The obtained comparison of heat removal methods made it possible to establish that heating with a nichrome spiral is optimal when the thickness of the coolant layer is 4 mm with a temperature difference of 1.2...2.4 °C. Under conditions of using FFREHRT, a temperature difference of 0.5...0.7 °C. This confirms the prospects of using FFREHRT in the RFA heating system in the conditions of a change in the feed rate of 0.5...1.5•103 kg/s. Thanks to the use of FFREHRT for RFA heating, operational conditions will be improved by simplifying the structural properties, reducing resource costs compared to heating with a heating shell with a coolant and the optimal temperature difference on the working surface of the apparatus.